MEMBONGKAR EPISTEMOLOGI PENDIDIKAN KI HADJAR DEWANTARA DALAM KONTEKS POSTMODERNISME - Rizki Ramadan (Yayasan An-Nur Meunara Baro, 2025)
This study deconstructs the educational epistemology of Ki Hadjar Dewantara (KHD) through the lens of postmodern critique. Using a deconstructive approach, the research investigates the relevance and reinterpretation of KHD’s concepts of the